STEM and Critical Thinking: Alternative Learning Collaboration between Teachers and Parents in The New Normal Era - Iva Nurmawanti; Darmiany; Nurwahidah; Anindita SHM Kusuma (SOSHUM : Jurnal Sosial dan Humaniora, 2021)
The ability to think critically must still be a focus on learning, especially in the era of the new normal. STEM at learning that focuses on the activity and the ability to think of students who integrate science, technology, engineering, and mathematics is one of the alternative learning in the era of the New Normal. Collaboration between teachers and parents in the implementation of learning with STEM integration is needed. It is caused, distance learning that is applied in the era of the New Normal implications at the time of learning of students is a lot at home. The results of this study indicated that STEM learning with collaboration between teachers and parents is suitable to be used as an alternative for learning in the new normal era, focus on students' critical thinking skills.